Quando o luto é luta , mobilização é ato criativo : experiências coletivas de jovens e mães em luta contra o genocídio da juventude negra - Rafaela Pereira Lima (2023)
The present study analyzes the communication processes for social mobilization built by two groups that fight against the genocide of black youth: the Greater BH Youth Forum (network that brings together collectives and youth entities from the Metropolitan Region of Belo Horizonte, MG) and the Mothers of Struggle Network (made up of groups of women whose family members had their rights violated and/or were murdered). The focus is on the processes of formation and movement of these two audiences, in addition to the public performance of the two networks in question: social struggles that take place in radical conditions, liminal between life and death. The thesis makes its contribution to Communication studies by building a decolonial perspective of analyzing publics in processes of social mobilization. During the research, a specific methodology was created for producing narratives of the activists' lives and struggles: a collaborative writing method involving each participating activist and the researcher, also an activist. To analyze the experiences, such narratives were the basis and outline of the discussions, based on a textual articulation inspired by the idea of the generating word, by Paulo Freire. Combining the description of the struggles with the reflections of the subjects that constitute them, the thesis demonstrates that the method of constructing public expression in the two networks analyzed is eminently experimental: based on open, problematizing, creative and transformative processes. In other words, it is a craftsmanship, a unique way of creating, whose logic is procedural: building the performance to give visibility to the struggle is, at the same time, building a different understanding of oneself, of the context in which it takes place. acts and the struggle itself. In the analysis presented, it is demonstrated that, in the journey between sharing the pain and anguish linked to the violence experienced by each person and collective action to give visibility to the struggle, something precious happens. There is a collective shaping of expression, which is a poetic act: the indistinct screams of pain and despair of those who suffer violence are the basis of a process of collective and collaborative modeling, from which they become a public cry for justice. Based on the analysis of several dimensions of this modeling process, the study argues that young people and mothers build a vigorous political action: in their performativity, they subvert the logics of racism, a prejudice rooted in Brazilian society. It concludes that the mode of action of these liminal struggles is embodied, experiential. What is experienced, in the processes discussed, is experiencing-as-struggle: the integral, vivid and intense experience of turning mourning into a struggle. In methodology, the thesis dialogues with the “ad-mirar” of Paulo Freire, the “escrevivência” of Conceição Evaristo, the afrographies of Lêda Maria Martins, the life stories of Karen Workman and the autobiographical narratives of Ecléa Bosi. In the theoretical discussion, it adopts a pragmatist and praxeological perspective, based on the concepts of public (Márcio Simeone Henriques and research group Institutions, Publics and Collective Experiences – Ipê, from UFMG), aesthetic experience (John Dewey) and event (Muniz Sodré and Ricardo Fabrino Mendonça). In the analysis of social mobilization processes, it highlights the collective construction of public performances of mourning and struggle, understanding such performances as crafts (inspired by The Artifice, by Richard Senett): creative acts (from Fayga Ostrower); expressive acts (based on Louis Queré's concept of narrative); poetic acts (based on Audre Lorde’s understanding of poetry: “revealing distillation of experience” – LORDE, 2019, p. 46; as well as self-construction and autopoiesis, by Humberto Maturana and Francisco Varela); political act (a formulation that draws on Judith Butler’s discussions of performativity and Jacques Rancière’s scene of dissent). Finally, based on the profound experiences of experimenting with life and art discussed, the thesis proposes a look at the experiential dimension of social mobilization (a discussion that articulates the concepts of unprecedented-viable, by Paulo Freire; experience, by Vygotsk; and to know, by Humberto Maturana).